Aplikasi model hidrologi HBV di DAS Peusangan Aceh sebagai studi pengantar pengembangan konsep ekohidrologi berkelanjutan - Yopi Ilhamsyah; Syahrizal Koem; Andi Syahid Muttaqin (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. A study of HBV hydrological model in Peusangan watershed Aceh as a preface study to the development of sustainable ecohydrological concept was done. The objective of the study was to apply and to test the HBV subtropical model into a tropical region Peusangan watershed. Peusangan watershed, situated in northern Aceh, covers an area of 2268.39 km2 and 128 km in length. The HBV model was manually calibrated by trial adjustment of each parameter to obtain the appropriate physical characteristics of Peusangan watershed. The result showed that the model was nearly consistent with the observation data. In fact, the correlation and error bias of the model were 0.623 and 0.11, respectively. However, the weakness of the model reported in the study is due to the coverage of the weather station data whi ch locate far in the downstream of Peusangan watershed. In the meantime, both of model result and observation showed a good agreement to catch the peakflow of Peusangan watershed. The two peakflow arise on May and October which were 212 m3dt-1 and 250 m3dt-1, respectively.Keywords. HBV Hydrological model, Peusangan watershed, peakflow